Odpowiedzi

2010-03-07T13:19:19+01:00
Zad.2
a)12-4a+5b-7+5a-4b-5=1a+1b-1
2010-03-07T13:20:57+01:00
Zad1.
a)4x - 2 <6
4x < 6+2
4x < 8 | /4
x < 2

b) -2x-4>-5x+5
-2x+5x > 5+4
3x>9 | /3
x >3

zad 2.
a)12-4a+5 b -7-(-5a)-4b-5 = 12-4a+5b-7+5a-4b-5 = -4a+5a+5b-4b+12-7-5 = a+b
b)5a³- 2ax³- a³x -4a³ = a³-2ax³-a³x
2010-03-07T13:21:07+01:00
Zad1.
a)4x - 2 <6
4x < 6 +2
4x < 8
x < 8:4
x < 2
b) -2x-4>-5x+5
-2x +5x > 5 +4
3x > 9
x > 9 :3
x > 3
zad 2.zredaguj wyrazy podobne
a)12-4a+5 b -7-(-5a)-4b-5 =
= 12-4a +5b -7 +5a -4b -5 =
= a +b
b)5a3- 2ax3 - a3x -4a3 =
= 5a³ - 2a³x - a³x - 4a³=
= a³ - 3a³x=
= a³( 1 -3x)
(trójki mają być w górze ) ;)